Is Plant Microbiota a Driver of Resistance to the Vector-Borne Pathogen Xylella fastidiosa? - Alejandro Cabezas-Cruz; Apolline Maitre (Pathogens, 2022)
Xylella fastidiosa is a vector-borne plant vascular bacterial pathogen that causes several economically important diseases, including Pierce’s disease (PD) in grapevine and olive quick decline syndrome (OQDS) in olive trees, among others [...]